Effect of lead ions on the sulfidization flotation of smithsonite using sodium butyl xanthate as a collector. (July 2022) - Luo, Bin; Nie, Wenlin; Dong, Jingshen
Graphical abstract: Highlights: The floatability of lead ion-activated smithsonite is superior to raw smithsonite. A new component (PbS) formed on the smithsonite surface after lead ion activation. The formation of PbS promotes sodium butyl xanthate adsorption. Lead ion activation increases number of active sites for collector adsorption. Abstract: Conventional sulfidization flotation with xanthate as a collector suffers from low smithsonite recovery owing to the instability of the sulfide layer. A new and effective activation method for the sulfidization flotation of smithsonite is therefore required; however, the development of such a method has proved challenging. In this study, the effect of lead ions on the sulfidization flotation of smithsonite was determined by flotation experiments using sodium butyl xanthate (NaBX) as a collector. Furthermore, the activation mechanism of lead ions in sulfidization flotation was systematically investigated by X-ray photoelectron spectroscopy, ultraviolet–visible spectrophotometry, time-of-flight secondary ion mass spectrometry, Fourier-transform infrared spectroscopy, and contact angle experiments. Lead ion activation leads to the formation of PbS on the smithsonite surface, which increases the adsorption activity and the number of active sites for NaBX, thereby significantly improving smithsonite recovery. Notably, NaBX reacted with the PbS on the smithsonite surface to form lead butyl xanthate (Pb(BX)2 ), which also enhanced the hydrophobicity of the smithsonite.